REVIEWING THE IMPACT OF COUNTRY-OF-ORIGIN ON CONSUMER PURCHASE INTENTION : THE ROLE OF CELEBRITY ENDORSEMENT IN EXISTING LITERATURE - Khan, Shanzara; Sookhai, Satesh (Universitas Nusa Cendana, 2025)
This paper explores the effect of country of origin on consumer purchase and repeat purchase intention. The moderating impact of celebrity endorsement will also be explored. This research took on a theoretical approach using over twenty-five (25) articles covering country of origin, purchase intention, and celebrity endorsement. Country-of-origin (COO) effects, namely cognitive, affective, and normative, alongside culture and consumer ethnocentrism, impact a consumer’s purchase intention. Consumers consider the specific effects of a product’s country of origin before purchasing a product, and international marketers must understand these. Research on repeat purchase intention shows no relationship with the country of origin as consumers are historically and sometimes emotionally tied to a product; therefore, they automatically purchase it without giving much thought to its country of origin. This study contributes to the existing literature while adding celebrity endorsement as an external variable. Thus, another important finding is how the theoretical theories of celebrity endorsement, namely, the source credibility model, the source attractiveness model, the match-up hypothesis, and the meaning transfer model, moderate the relationship between the COO effect and purchase and repeat purchase intention. Keywords: Country-of-Origin; Consumer Purchase Intention; Repeat Purchase Intention; Celebrity Endorsement